Strong, tough and healable elastomer nanocomposites enabled by a hydrogen-bonded supramolecular network. (December 2020) - Li, Jiajun; Zhang, Ping; Chen, Lin; Li, Gaoming; Chen, Hao; Jia, Chunhui; Wu, Yeping; Chen, Mao; Zhao, Xiuli; Song, Pingan
Abstract: Epoxidized natural rubber (ENR)/organic-modified layered double hydroxide (O-LDH) nanocomposites were prepared in this work. The O-LDH can participate in the formation of a hydrogen-bonded supramolecular network in the ENR matrix. The network can effectively improve mechanical properties. With 20 phr O-LDH, the stress, strain and Young's modulus of the final ENR/O-LDH nanocomposite increase to 2.80 MPa, 542% and 4.70 MPa, which is 366%, 113% and 427% of the neat ENR, respectively. Meanwhile, the ENR/O-LDH nanocomposites show self-healing behavior due to the dynamic hydrogen-bonded supramolecular network and chain diffusion. The ENR/O-LDH-10 exhibited the highest self-healing efficiency of about 78% (120 °C, 12 h). When the O-LDH content exceeds 10 phr, the restricting effect of fillers weakens the ability to reconstruct hydrogen-bonding, and thus reduces the healing efficiency of the ENR nanocomposites, despite continuous increased mechanical properties. This work opens up many opportunities for creating advanced elastomers that are strong, tough and self-healable through the design of a dynamic supramolecular network. Graphical abstract: Image 1 Highlights: High-performance epoxidized natural rubber (ENR) nanocomposites are prepared. Organic-modified layered double hydroxide (O-LDH) are added to the ENR. A hydrogen-bonded supramolecular network forms between the ENR and O-LDH. Tensile stress and break strain of the ENR increase by 366% and 113%, respectively. The ENR nanocomposites with 10 phr O-LDH shows a high healing efficiency of 78%.